If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1y = 2x + y Solving x + -1y = 2x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. x + -2x + -1y = 2x + -2x + y Combine like terms: x + -2x = -1x -1x + -1y = 2x + -2x + y Combine like terms: 2x + -2x = 0 -1x + -1y = 0 + y -1x + -1y = y Add 'y' to each side of the equation. -1x + -1y + y = y + y Combine like terms: -1y + y = 0 -1x + 0 = y + y -1x = y + y Combine like terms: y + y = 2y -1x = 2y Divide each side by '-1'. x = -2y Simplifying x = -2y
| 2x-20+70-x=180 | | 7x+46z+2y=43a+18b | | 7z+46x+2y=43a+18b | | b=46x+2y+7z | | 46b+2y+7z=x | | 46x+2y+7z=b | | 4p^2+25p+6=0 | | 46x+2y+7z=43a+18b | | 240=2w^2+4w | | x+y=73 | | 2m^2-3m-27=0 | | 5n/2 | | 8n/3n+7 | | 28=4w+4 | | 28=w^2+2w+4 | | 0=-2x^2-8x+10 | | (2x+5)/5=(3x+1)/2+(-x+7)/2 | | (x-8)/5+(8)/5=(-x)/3 | | 16x^3y-40x^2y^2+25xy^3=0 | | 3/(4+t)+8=4 | | 16x^3y-40x^2y+25xy^3=0 | | 6+4x+7x+4x=16x-1 | | 4x+3+7x+4x+3=16x-1 | | 3x-23y=-11 | | .5x+19.3=x-2.05 | | 128x^2=8 | | x^3-4x^2=-9 | | (7x+25)/5 | | 4-4=3w-2w+5 | | 5a+7b-3+3b-2a+8= | | -8v+3(v+6)=-12 | | e=k+32.2m |